DEVELOPMENT POTENTIAL OF NAGARA BEAN (Vigna unguiculata ssp. Cylindrica) CULTIVATED IN FRESHWATER SWAMPLANDS FOR PROCESSED FOOD - Hustiany, Rini; Rahmawati, Emy; Rahmi, Alia (The Journal is published by Graduate Programe of Lambung Mangkurat University, 2016)
Nagara bean/ catjang (Vigna unguiculata spp. Cylindrica) is a subspecies of cowpea which is widely cultivated in freshwater swamplands of Daha Utara and Daha Selatan sub-districts, Hulu Sungai Selatan Regency. Nagara bean is a plant native to South Kalimantan, but its utilization is still very low compared to other cowpeas. The aims of this study were to analyze the chemical and physical characteristics of Nagara bean in processed food compared to those of soybeans; and to analyze the development potential of Nagara bean in processed food. The methods were the production of catjang flour from skinless Nagara beans; the production of catjang flour by roasting Nagara beans; the substitution of Nagara beans with coagulated and fermented soybeans. The results showed that the flour from skinless Nagara beans contained protein (24.16%) and carbohydrate (61.62%), while the flour from roasted Nagara beans contained protein (18.42%) and carbohydrate (69.33%). When compared to soybeans, papan and arabian beans, the two types of Nagara bean, could be coagulated with a higher water content and lower protein content. When Nagara beans were fermented, the water and protein contents of fermented beans were higher than those of soybeans. It can be concluded that Nagara beans could be used in processed foods chemically. Nagara beans however absorbed water easily, so they smelled sour and unpleasant and the texture became soft.